Exploring political communication through data mining: A case study of the 2024 Indonesian presidential election - Karim, Abdul (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This study aims to explore the perceptions of social media users (netizens) towards the 2024 presidential candidates of the Republic of Indonesia through sentiment analysis and political communication expressions. Secondary data was collected using the Application Programming Interface (API) of social media platforms by utilising programming algorithms for the data collection and analysis process. The study population consisted of tweets discussing 2024 presidential candidates on platform X and YouTube, with a sample size of 50,000 data. The results revealed significant trends in netizen sentiment and communication patterns, providing implications regarding netizen political engagement and opinions. This study concludes that the dynamics of political discourse in Indonesia's digital realm have important implications to be understood in the context of general elections. In addition, this research contributes to emphasizing the important role of digital media in the political context, especially political communication. ***** Penelitian ini bertujuan untuk mengeksplorasi persepsi pengguna media sosial (netizen) terhadap calon presiden Republik Indonesia 2024 melalui analisis sentimen dan ekspresi komunikasi politik. Data sekunder dikumpulkan dengan menggunakan Application Programming Interface (API) platform media sosial dengan memanfaatkan algoritma pemrograman untuk proses pengumpulan dan analisis data. Populasi penelitian terdiri dari tweet yang membahas calon presiden 2024 di platform X dan YouTube, dengan jumlah sampel sebanyak 50.000 data. Hasil penelitian menunjukkan tren yang signifikan dalam sentimen netizen dan pola komunikasi, yang memberikan implikasi terkait keterlibatan dan opini politik netizen. Penelitian ini menyimpulkan bahwa dinamika wacana politik di ranah digital Indonesia memiliki implikasi yang penting untuk dipahami dalam konteks pemilihan umum. Selain itu, studi ini berkontribusi dalam menegaskan peran penting media digital dalam konteks politik terutama komunikasi politik.